2014
DOI: 10.1109/surv.2013.062613.00014
|View full text |Cite
|
Sign up to set email alerts
|

On Swarm Intelligence Inspired Self-Organized Networking: Its Bionic Mechanisms, Designing Principles and Optimization Approaches

Abstract: Inspired by swarm intelligence observed in social species, the artificial self-organized networking (SON) systems are expected to exhibit some intelligent features (e.g., flexibility, robustness, decentralized control, and self-evolution, etc.) that may have made social species so successful in the biosphere. Self-organized networks with swarm intelligence as one possible solution have attracted a lot of attention from both academia and industry. In this paper, we survey different aspects of bioinspired mechan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
36
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 213 publications
(36 citation statements)
references
References 133 publications
0
36
0
Order By: Relevance
“…The thoughts and methods of swarm intelligence have been also applied to improve the capabilities of self-organized or adaptive systems. For instance, Zhang et al concluded the principles and optimization approaches [28], and Wong et al surveyed how to employ these techniques to enhance the learning ability of adaptive systems [29].…”
Section: Swarm Intelligence Theoriesmentioning
confidence: 99%
“…The thoughts and methods of swarm intelligence have been also applied to improve the capabilities of self-organized or adaptive systems. For instance, Zhang et al concluded the principles and optimization approaches [28], and Wong et al surveyed how to employ these techniques to enhance the learning ability of adaptive systems [29].…”
Section: Swarm Intelligence Theoriesmentioning
confidence: 99%
“…Surveys focused on CR communications in isolation have considered the general principles of CR communications [20], [26]- [30] as well as CR network structures [31]- [37]. Studies on spectrum occupancy modeling and spectrum sensing have been surveyed in [38]- [44], while mechanisms for spectrum access and radio channel resource assignment have been covered in [45]- [57].…”
Section: Review Of Related Survey Articlesmentioning
confidence: 99%
“…In 2003, the US Natural Science Foundation Committee developed a sensor network research program, investment million dollars to support the basic theory of the study. Under the auspices of the Natural Science Foundation of the United States, the University of California at Berkeley, Massachusetts Institute of Technology, Cornell University and the University of California began to study the basic theory and key technologies of sensor networks [10].…”
Section: State Of the Artmentioning
confidence: 99%